Ninety day mortality following pancreatoduodenectomy in England: has the optimum centre volume been identified?. Issue 11 (November 2018) - Liu, Z.; Peneva, I.S.; Evison, F.; Sahdra, S.; Mirza, D.F.; Charnley, R.M.; Savage, R.; Moss, P.A.; Roberts, K.J.
Abstract: Background: Mortality following pancreatoduodenectomy is related to centre volume although the optimal volume is not defined. Methods: Patients undergoing PD between 2001 and 2016 were identified from UK national databases. The effects of patient variables, centre volume and time period upon 90 day mortality were studied. Results: 90 day mortality (970/14, 935, 6.5%) was related to advanced age, comorbidity, diagnosis, ethnicity, deprivation, centre volume and time period. Mortality rates fell markedly from 10.0% in 2001-4 to 4.1% in 2013-16. There was no difference in 90 day mortality between high (36 -60 PD per year) and very high volume (>60) centres. However, patients operated upon at very high volume centres were more elderly (66, 58 -73 vs 65, 56 -72; median, IQR; p = 0.006), deprived (38.7 vs 34.6%; p < 0.001) and co morbid (48.9 vs 46.1%; p = 0.027). Conclusion: Although a plateau in the centre volume and mortality relationship appears to have been demonstrated those patients treated at the highest volume centres were at higher risk of mortality. This data suggests therefore that to further understand outcomes from specialist centres characteristics of the patient population should be defined, not just centre volume.